Pengukuran Kinerja Industri Kelapa Sawit Menggunakan Metode Balanced Scorecard dan Proses Hirarki Analitis - Saleh, Anis; Herdianzah, Yan; Padhil, Ahmad; Fole, Asrul; Ahmad, Arfandi; Safutra, Nur Ihwan; Rasyiqah, Alifah (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2024)
Palm oil plantations are one of the agricultural commodities in Indonesia that play a crucial role in food availability and the economy. This research employs the Balanced Scorecard (BSC) model as an integrated performance measurement system. The BSC measures company performance from both financial and non-financial perspectives. The study aims to measure the performance of the palm oil industry at PT. KMP Masamba, and covers four perspectives namely financial, customer, internal business, and learning and growth. The weighting of performance measurement elements is done using the analytical hierarchy process with the assistance of Expert Choice software. The results are expected to assist PT. KMP Masamba in determining necessary improvement priorities. The performance measurements from each perspective, ranked from highest to lowest, are as follows: customer perspective (0.148), internal business perspective (0.048), learning and growth perspective (0.047), and financial perspective (0.030). The overall company performance score is 0.543, indicating satisfactory performance and approaching high targets. Based on these conclusions, recommendations for this research include periodic performance measurement by the company to assess its comprehensive condition and improve functional activities with low performance, to improve their performance indicators.Keywords - Analytical Hierarchy Process, Balance Scorecard, The Performance Measurements.